Resolution of Fundic Gland Polyposis following Laparoscopic Magnetic Sphincter Augmentation and Subsequent Cessation of Proton Pump Inhibitors - Joel R. Brockmeyer; Erin E. Connolly; Richard J. Wittchow; Shanu N. Kothari (Case Reports in Gastrointestinal Medicine)
Gastric polyps occur from a variety of sources and are found commonly on upper endoscopy. We present the case of a 49-year-old female who presented for evaluation for antireflux surgery with a history of fundic gland polyposis who required twice-daily proton pump inhibitors (PPIs) for control of her gastric reflux. After verifying that she met criteria for surgery, she underwent an uncomplicated laparoscopic magnetic sphincter augmentation placement. With the cessation of PPIs following surgery, the fundic gland polyposis resolved. Fundic gland polyps may occur sporadically or within certain syndromes, such as familial adenomatous polyposis. Multiple possible inciting factors exist, including the use of PPIs. This is the first reported case of the resolution of numerous fundic gland polyps following the completion of laparoscopic magnetic sphincter augmentation.